Pilocytic Astrocytoma with Specific Gene Signature - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Researchers at Universite de la Mediterranee, and other centers in Marseille, France, using the microarray technique to compare the transcriptional profiles of five optic pathway, hypothalamo-chiasmatic and six cerebellar pilocytic astrocytomas, found that these 2 tumors are genetically distinct and topography-dependent entities.